POLEMIK KETENTUAN PENJAMIN DAN PENETAPAN BATAS TANAH MENURUT PMNA/KPBN NO 3 TAHUN 1997 SEBAGAI KEWAJIBAN PEMOHON - Ridho Sa’dillah Ahmad; Febri Tri Siami (JUNAGARA: Jurnal Ilmiah Hukum dan Kenegaraan, 2024)
Land frequently creates issues and turns into a wellspring of contention in the public eye. despite the fact that the community itself consistently desires legal certainty regarding their rights to the land they own or control. Accurate evidence is required to clarify and recognize these land parcels. Typically, individuals only have a Land Declaration Letter (SPT). The legal basis for tenure rights over land parcels continues to be based on documents whose strength of proof is still weak. The incongruity is that there are still bundles of land that don't have clear limits, in this way giving an opening to specific individuals to guarantee privileges over others' property. In order to prevent irresponsible parties from easily moving or shifting boundary signs, they must be made clear. A fundamental map for land registration is built on boundary signs. Therefore, if the boundary markers are only growing plants, flimsy ditches and wooden stakes that are not long-lasting can create legal and rights uncertainty.